2020
DOI: 10.1002/jts.22629
|View full text |Cite
|
Sign up to set email alerts
|

Mastery, Social Support, and Sense of Community as Protective Resources Against Psychological Distress Among Israelis Exposed to Prolonged Rocket Attacks

Abstract: We investigated the psychological toll of exposure to rocket attacks as experienced by residents of central and southern Israel during the 2014 Israel–Gaza conflict. Participants completed an online survey assessing their life‐threatening experiences, the availability of psychosocial resources, and symptoms of both PTSD (PCL‐5) and nonspecific psychological distress (K6) 2–3 months posttrauma. Guided by the conservation of resources theory, we focused on the distress‐protective functions of person‐ and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Although there are many studies documenting protective functions of community resources against psychological distress (e.g., Gelkopf et al, 2012; Zanbar et al, 2018), there are also studies that showed null effects (e.g., Johns et al, 2012). Moreover, other investigations reported that posttrauma higher levels of community engagements, under some conditions, may be associated with poorer psychological outcomes (e.g., Ben-Tzur, Zanbar,& Kaniasty, in press; Gallagher et al, 2019; Somer et al, 2008; Zanbar et al, 2018). There are several clashing psychological and social dynamics that may compromise the usually expected beneficial influence of social and community relationships on well-being (see Villalonga-Olives, & Kawachi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies documenting protective functions of community resources against psychological distress (e.g., Gelkopf et al, 2012; Zanbar et al, 2018), there are also studies that showed null effects (e.g., Johns et al, 2012). Moreover, other investigations reported that posttrauma higher levels of community engagements, under some conditions, may be associated with poorer psychological outcomes (e.g., Ben-Tzur, Zanbar,& Kaniasty, in press; Gallagher et al, 2019; Somer et al, 2008; Zanbar et al, 2018). There are several clashing psychological and social dynamics that may compromise the usually expected beneficial influence of social and community relationships on well-being (see Villalonga-Olives, & Kawachi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Hebrew version of the Post-Traumatic Stress Checklist for DSM-5 [PCL-5; ( 59 )] is a 20-item standardized and clinically validated self-report measure assessing PTSD as defined by the DSM-5. We used the Hebrew version of the PCL-C 5, which has been widely used and has shown good psychometric properties [e.g., ( 60 , 61 )]. Mothers completed the Hebrew version of the PCL-C (civilian version), in which the items refer to PTSS related to a traumatic experience.…”
Section: Methodsmentioning
confidence: 99%
“…A sense of community promotes resilience and has frequently been shown to correlate with positive psychological outcomes in the wake of potentially traumatic events (Ben-Tzur et al, 2021). Individuals who express more connections to their communities exhibit lower levels of distress (e.g., Dekel & Tuval-Mashiach, 2012; Gelkopf et al, 2012; Levy & Friedman, 2019).…”
Section: Associations Between the Study Variablesmentioning
confidence: 99%